1993
DOI: 10.1002/bem.2250140503
|View full text |Cite
|
Sign up to set email alerts
|

Effects of time‐varying uniform magnetic fields on Natural Killer cell activity and antibody response in mice

Abstract: Natural Killer cell activity and antibody response were studied in Balb/c mice which were exposed in vivo to uniform pulsed magnetic fields (square-wave, 0.8 Hz, 120 mT maximum field strength, 0.1 s rise-time) for 5 days, 10 h/day. No effects were found in antibody response to sheep red blood cell (SRBC) immunization as assayed by counting the plaque-forming cells (PFC) in the spleens of animals on the sixth day. Following 5-day exposures, the activity of Natural Killer (NK) cells was measured in vitro by chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…According to the results of these studies, MF activates natural killer cells (De Seze et al 1993), stimulates IL-4 synthesis (Salerno et al 1999), reduces the severity of pain (Colbert et al 2008), and when antitumour drugs were used in combination with a weak MF the tumorigenesis was suppressed (Omote et al 1990). In addition, thermal radiation has been known to play a very important role for a very long time in the treatment of various diseases.…”
Section: Effect Of Magnetic Field On Enzyme Activitymentioning
confidence: 99%
“…According to the results of these studies, MF activates natural killer cells (De Seze et al 1993), stimulates IL-4 synthesis (Salerno et al 1999), reduces the severity of pain (Colbert et al 2008), and when antitumour drugs were used in combination with a weak MF the tumorigenesis was suppressed (Omote et al 1990). In addition, thermal radiation has been known to play a very important role for a very long time in the treatment of various diseases.…”
Section: Effect Of Magnetic Field On Enzyme Activitymentioning
confidence: 99%
“…e l s e v i e r . c o m / l o c a t e / a q u a -o n l i n e alternating magnetic field or an 80 mT steady magnetic field increased immune function in mice (Seze et al, 1993). Similarly, Ding and Wang (1998) exposed tumor-burdened mice to a magnetic field and noted an increase in the weight of the thymus and spleen and increased body weight gain consistent with an improved immune response.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 90%
“…Moreover, some proteins and enzymes that contain metal ions exhibit paramagnetism (Schenck, 1996). Because these ions are in the enzyme activity center (Lin et al, 1992), they affect the reaction speed of biochemical reactions and thereby the growth rate (Seze et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Sachiko Yamaguchi et al [2][3] observed that plenty of necrotic areas were induced within the tumor issue of C57BL/6J mice post-PMF (amplitude of 0.25 T, pulse width of 238 µs, and repetition frequency of 25 Hz) treatment. Rene de Seze et al [4][5] used a square wave pulse magnetic field with amplitude of 100 mT and repetition frequency of 0.8 Hz to treat three kinds of mice, namely, Balb/c, C3H, and C57/bl/6, for 8 h per day. The statistical results indicate that tumor growth has been significantly inhibited.…”
Section: Introductionmentioning
confidence: 99%